Tourism Components Analysis and Sustainable Rural Tourism Development Planning Based on Culture and Agriculture in Indonesia (Case Study: Cimande Village) - Dina Mayasari Soeswoyo; Putu Swasti Asparini Syahrijati; Dimas Aryo Baskoro; Damas Aryo Anggoro; Mega Jayanti Sutisna (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of this study is to describe the tourism component of Cimande Village as well as its development plan as a sustainable tourism village. This study was carried out between 2018 and 2021, employing a qualitative method and a case study strategy. The technique of collecting data is through repeated in-depth observations, interviews, and literatures study. Data were analyzed using six (6) key components of tourism planning, namely tourist attractions & activities, accommodation, other tourist facilities and services, transportation, infrastructure, and institutional elements. Other analytical techniques used are internal and external factors analysis, as well as SWOT Matrix. The findings revealed that Cimande Village has a lot of tourism potential, especially in cultural and agricultural attractions. Its potentials can be mapped on 53 internal and external factors, as well as 22 plans for a sustainable tourism village development.